The short outcomes and in-hospital complications in patients with STEMI revascularized with primary PCI: A prospective registry from India - Singh, Ambukeshwar; Narain, Varun; Sharma, Jayesh; Chaudhary, Gaurav; Vishwakarma, Pravesh; Yadav, Sharad; Dwivedi, Sudhanshu (Research in cardiovascular medicine, 2022)
Context: Primary percutaneous coronary intervention (PCI) is the most effective reperfusion therapy with low complication rate in comparison to thrombolysis. Aims: We aimed to study the short-term outcomes of primary PCI at a large tertiary care center in India. Settings and Design: A prospective cohort of patients with ST-elevation myocardial infarction (STEMI) who underwent primary PCI was enrolled between December 2015 and November 2016. Subjects and Methods: The demographic profile, risk factors, clinical characteristics, inhospital complications, and outcomes at 30 days were assessed. The primary outcome was a composite of death, reinfarction, and repeat revascularization. Acute left ventricular failure (LVF), complete heart block (CHB) or bradyarrhythmia, ventricular tachycardia (VT) or ventricular fibrillation, stroke, and major thrombolysis in myocardial infarction bleeding were the inhospital complications that were considered the secondary outcomes. Results: A total of 237 STEMI patients with primary PCI were enrolled, accounting for 7.5% of all PCI procedures performed during this period. The mean age was 55.4 ± 11.9 years, and 86.5% were male. The mean window period was 5.1 ± 3.18 h, and the mean door-to-balloon time was 58.4 ± 11.5 min. Prior to PCI, the most often administered antiplatelets were clopidogrel in 54.4% of patients and prasugrel in 55.6%. The aspiration thrombectomy was done in 70.8% of patients. Predilatation with balloon was required in 41.8% of patients. Drug-eluting stents were implanted in 98.3% of patients. The primary outcome was found in 3.3% of patients (deaths - 2.9% and reinfarction - 0.4%) and the secondary outcomes were observed in 13%. The common inhospital complication was CHB or bradyarrhythmia in 5.0% followed by acute LVF in 4.6% and then VT in 2.1%. Conclusions: The primary outcome rate is as good as reported in developed Western countries in contemporary treatment practices of STEMI. CHB and acute LVF were the major inhospital complications among patients of STEMI treated with primary PCI.